The Effectiveness of Supportive Psychotherapy on the Anxiety and Depression Experienced by Patients Receiving Fiberoptic Bronchoscope - Ren, Fengjuan; Ruan, Dan; Hu, Weilin; Xiong, Yan; Wu, Yuwan; Huang, Siyu (Frontiers in Psychology, 2022)
Objectives: As the largest cohort of healthcare workers, nurses can practice as psychotherapists to integrate the psychotherapeutic interventions as part of routine care. The present study aims to evaluate the effectiveness of supportive psychotherapy (SPT) on patients who had been scheduled to undergo fiberoptic bronchoscopy (FOB) procedure. Methods: This study retrospectively analyzed 92 patients who underwent FOB, which were divided into the SPT group and usual-care group based on whether patients were given SPT interventions or not. The Patient Health Questionnaire-9 (PHQ-9) and Hospital Anxiety and Depression Scale (HADS) were used to determine the severity of depression and anxiety, as well as 36-Item Short Form Health Survey questionnaire (SF-36) to evaluate the health-related quality of life (HRQoL). Moreover, the patients’ satisfaction was assessed based on the Likert 5-Point Scale. Results: The baseline status of anxiety, depression, and HRQoL in patients was similar in the SPT group and the usual-care group with no significant difference. Both PHQ-9 score and HADS-D score in the SPT group after intervention was lower than that in the usual-care group, accompanying by deceased HADS-A subscale. Moreover, the improved HRQoL was found in the patients undergoing FOB after SPT interventions as compared to those received conventional nursing care using SF-36 score. Additionally, and the patient’ satisfaction in the SPT group was higher than the usual-care group. Conclusions: The study demonstrated that anxiety and depression, as negative emotions, can be reduced by supportive psychotherapy in patients receiving FOB with improved mental health and satisfaction with nursing care.